RESPONSE OF SEEDLINGS Biota oreintalis Endl TO ORGANIC MANURE (POW HUMUS) AND GIBBERELLIC ACID (GA3) SPRAYED ON VEGETATIVE GROWTH - Mudhafar Abdullah; Muhammed Hamid Muhammed (Mesopotamia Journal of Agriculture)
This study has been conducted at the nursery of Forestry Department , College of Agriculture and Forestry , Mosul University , Mosul , Iraq.from the beginning of march until the end of December , 2012. This study was to investigate the effect of concentrations of organic manure (zero , 1, 2 gm/l) and the concentrations Gibberellic Acid (zero , 20 ,40 mg/l) and sprayings occation (two and four) on the growth of Biota oreintalis Endl. seedlings. The following characters were studied: increase of growth length (cm), Stem diameter (mm), increase of number of branches per seedling , Main root length (cm) , Main root diameter (mm). So results can be summarized as follows: The concentrations of organic manure effected significantly in all characters and concentration (1 gm / l) caused significant increase in all characters. Spraying with (40 mg/l) of gibberellic acid caused significant increase in the average of characters. The results showed that the best sprayings occation was (four times) for most characters in comparison with (two sprayings). The interaction between concentration organic manure (1 gm /l) and concentration gibberellic acid (40 mg/l) effected significantly in characteristics. The effect of interaction No.2 between concentration organic manure (1 gm /l) and sprayings times (four sprayings) caused significant increase in the average of the characters. The effects of interaction with gibberellic acid (40 mg /l) and sprayings occation (four sprayings) effected significantly in all characters studiced. The results of triple interaction between (concentration organic manure and concentration gibberellic acid and sprayings occation) interaction (1gm /l organic manure, 40 mg / l gibberellic acid and four sprayings) was superior in increase of growth length, Stem diameter, increase of number of branches , Main root length , Main root diameter.